Experimental evidence of an electronic transition in CeP under pressure using Ce L3 XAS. Issue 27 (28th June 2017) - Joseph, B.; Torchio, R.; Benndorf, C.; Irifune, T.; Shinmei, T.; Pöttgen, R.; Zerr, A.
Abstract : A direct compelling evidence of an electronic transition associated with the isostructural unit-cell volume discontinuity in CeP under pressure is provided using Ce L3 -XAS. A DAC with a combination of a mini and a partially perforated anvils made of nanodiamonds permitted us to track the pressure induced changes in the 4f state of Ce in CeP. Abstract : Cerium phosphide undergoes a unit-cell volume discontinuity without any structural phase transitions upon application of a high pressure of ∼10 GPa. This phenomenon is attributed to a change in the electronic charge distribution of the cerium in CeP, but to date no direct experimental verification for this hypothesis has been presented. Here, we report a Ce L3 -edge X-ray absorption spectroscopy study under pressure, which provides direct compelling evidence of an electronic transition associated with the above-mentioned isostructural volume discontinuity. The present results should be relevant to the understanding of the phenomenon of pressure induced isostructural transitions involving unit-cell volume collapse.